The evolution of female voice acoustics: A lifespan perspective - Suprent, Ambethkar; Samayan, Dr.Kala (South Eastern European Journal of Public Health, 2024)
Aim: The aim of this study is to develop normative measures of selected vocal acoustic parameters among females aged 6 to 70 years. The following parameters were selected for analysis: Fundamental Frequency (Fo), Jitter, Relative Average Perturbation (RAP), Shimmer (dB), and Noise to Harmonic Ratio (NHR). Methods: A total of 270 female participants were included in the study, with 30 individuals in each of the 9 age groups. Each participant provided a phonation of the vowel /a/ for analysis. Material: The vowel /a/ was used as the stimulus for vocal recording. The Computerized Speech Lab (CSL 4500B) software module for Multi-Dimensional Voice Profile (MDVP) was utilized to analyze the vocal responses. Results: The results revealed significant differences in all the vocal parameters across the age groups. These differences reflect the age-related changes in the acoustic characteristics of the female voice. Conclusion: This study provides a comprehensive assessment of the acoustic variations in the female voice across a broad age range, offering valuable insights into the effects of aging on vocal quality. By employing standardized recording techniques and advanced acoustic analysis methods, this research adds to the growing body of literature on vocal changes throughout the human lifespan. The findings can serve as a reference for future studies in clinical voice assessment, speech therapy, and voice technology.